IMPROPER AGRICULTURAL PRACTICES LEAD TO LANDSLIDE AND MASS MOVEMENTDISASTERS: A CASE STUDY BASED ON UPPER MADI WATERSHED, NEPAL - Gurung, Anup; Gurung, Om Prakash; Karki, Rahul (Emirates Journal of Food and Agriculture, 2017)
Damage, destruction, and fatalities related to landslide and mass movement are common phenomena in the Himalayan countries like Nepal, especially during the monsoon period. In Nepal, landslides represent a major constraint on livelihood and development, causing high levels of economic loss and substantial casualties each year. This fact was tragically illustrated on 3 August 2010, when Nang-Nung of Taprang, situated at the 22 km away from the Pokhara valley, upper Madi watershed, experienced a catastrophe landslide powered by the Madi river. The landslide and the debris flow caused widespread damage to life and property and destroyed valuable infrastructure in the area and the adjoining villages. 72 houses were swept away, 59 houses were partially damaged, 58.4 ha of land was washed away, 6 people were wounded, 5 people were killed, and many social infrastructures were damaged. The disaster was a result of a landslide triggered by heavy precipitation and stream undercutting the existing landslide.